(untitled) (Journal of Educational Sciences, 2017)
The purpose of this article is determination of academic mobility and academic freedom on the base polylinguism as elements of the internationalization of education in Kazakhstan. The modern trend of internationalization of Kazakhstani education is impossible to imagine without the development of polylinguism, part of which is the knowledge of the English language as the language of globalization. Currently, English is the language of modern science, since 90% of scientific information is produced in English. Polylinguism is an important trend of modern Kazakhstani education, making it an international and competitive in a global world. The article addresses important issues of multilingual education: development of academic freedom, academic mobility, language training for students and teachers, theoretical and practical goals of internationalization on the basis of empirical data Key words: polylinguism, academic mobility, academic freedom, internationalization, modernization.